Considerations for assessing frail older adults requesting medical assistance in dying - Engelhart, Sarah; Stall, Nathan M.; Quinn, Kieran L. (Canadian Medical Association journal (CMAJ), 2022)
In 2016, medical assistance in dying (MAiD) was decriminalized in Canada with the passage of Bill C-14. Under Bill C-14, competent adults with a serious and incurable condition in an advanced state of irreversible decline who were experiencing intolerable physical or psychological suffering and whose death was reasonably foreseeable could be eligible for MAiD. After its passage, legal challenges were brought before the Superior Court of Quebec, who ruled that the original legislation was too restrictive and in violation of the Canadian Charter of Rights and Freedoms. This led to the passage of Bill C-7 in Mar 2021, which amended Canada's criminal code to remove "reasonably foreseeable death" as an eligibility criterion, thus creating 2 distinct pathways for MAiD, where death either is or is not reasonably forseeable. One patient population likely to be affected by these changes is older adults considered to be frail. Clinicians should consider whether factors contributing to frailty are reversible when considering requests for MAiD. MAiD for those in whom death is not reasonably forseeable is subject to additional safeguards including a minimum 90-day period for assessing eligibility and mandatory assessment by a clinician with expertise in the patient's condition.